GeoSAR Feasibility Study: Summary of the Group Design Project. MSc in Astronautics and Space Engineering 2012/13 - Hobbs, Stephen (Cranfield University, 2013)
Students of the MSc course in Astronautics and Space Engineering 2012–13 at Cranfield University performed a feasibility study of a geosynchronous radar mission for their group project. This report summarises the students’ work and their findings. The report consists of an overview and discussion of the technical work of the project and a compilation of the executive summaries which describe the specific contributions of each student. The mission studied is a Ku-band monostatic SAR in a small inclination (80 km relative orbit diameter) geosynchronous orbit. The total launch mass is 2 tonnes, and images with resolution 40 m to monitor land subsidence in urban areas are produced. The mission appears to be feasible within the scope of an ESA Earth Explorer proposal.